Phenotypic Characterization of Circulating CD4+ T Cells in ANCA-Associated Vasculitis - Sandra Lilliebladh; Åsa Johansson; Åsa Pettersson; Sophie Ohlsson; Thomas Hellmark (Journal of Immunology Research)
T cell-mediated immune responses are thought to play an important role in the pathogenesis of anti-neutrophil cytoplasmic antibody- (ANCA-) associated vasculitides (AAV). CD4+ T cells can be divided into subsets depending on their expression of chemokine receptors. In this study, different CD4+ T cell populations in patients with AAV were analysed and compared to healthy blood donors as well as therapy controls. 18 patients with active AAV, 46 in remission, 21 healthy controls (HBD), and 15 therapy controls (TC) were enrolled. CD4+ T cells were divided into Th1, Th2, and Th17 cells and further subdivided into naïve, central memory, effector memory, and effector cells. Regulatory T cells were also analysed. Concentrations of cytokines and chemokines produced by the respective CD4+ T cell subset in plasma from 33 of the patients were measured by ELISA and compared to HBD. Clinical data were collected on all patients. CCL20 concentrations and percentages of Th17 cells (p=0.019) were elevated in AAV patients compared to HBD. AAV patients had lower percentages of naïve CD4+ T cells (p=0.0016) and a corresponding increase in proportion of effector memory CD4+ T cells when comparing to HBD (p=0.027). Therapy controls showed similar results as AAV patients. In this study, we found that CD4+ T cell phenotype distribution is altered in AAV patients, in line with previously published work. However, no differences were found between AAV patients and TC, stressing the importance of treatment impact on this kind of studies.